Impact of prolonged sepsis on neural and muscular components of muscle contractions in a mouse model. Issue 2 (19th January 2021) - Goossens, Chloë; Weckx, Ruben; Derde, Sarah; Van Helleputte, Lawrence; Schneidereit, Dominik; Haug, Michael; Reischl, Barbara; Friedrich, Oliver; Van Den Bosch, Ludo; Van den Berghe, Greet; Langouche, Lies
Abstract: Background: Prolonged critically ill patients frequently develop debilitating muscle weakness that can affect both peripheral nerves and skeletal muscle. In‐depth knowledge on the temporal contribution of neural and muscular components to muscle weakness is currently incomplete. Methods: We used a fluid‐resuscitated, antibiotic‐treated, parenterally fed murine model of prolonged (5 days) sepsis‐induced muscle weakness (caecal ligation and puncture; n  = 148). Electromyography (EMG) measurements were performed in two nerve–muscle complexes, combined with histological analysis of neuromuscular junction denervation, axonal degeneration, and demyelination. In situ muscle force measurements distinguished neural from muscular contribution to reduced muscle force generation. In myofibres, imaging and biomechanics were combined to evaluate myofibrillar contractile calcium sensitivity, sarcomere organization, and fibre structural properties. Myosin and actin protein content and titin gene expression were measured on the whole muscle. Results: Five days of sepsis resulted in increased EMG latency ( P  = 0.006) and decreased EMG amplitude ( P  < 0.0001) in the dorsal caudal tail nerve–tail complex, whereas only EMG amplitude was affected in the sciatic nerve–gastrocnemius muscle complex ( P  < 0.0001). Myelin sheath abnormalities ( P  = 0.2), axonal degeneration (number of axons; P  = 0.4), and neuromuscular junction denervation ( P  = 0.09) were largely absent in response to sepsis, but signs of axonal swelling [higher axon area ( P  < 0.0001) and g ‐ratio ( P  = 0.03)] were observed. A reduction in maximal muscle force was present after indirect nerve stimulation ( P  = 0.007) and after direct muscle stimulation ( P  = 0.03). The degree of force reduction was similar with both stimulations ( P  = 0.2), identifying skeletal muscle, but not peripheral nerves, as the main contributor to muscle weakness. Myofibrillar calcium sensitivity of the contractile apparatus was unaffected by sepsis ( P  ≥ 0.6), whereas septic myofibres displayed disorganized sarcomeres ( P  < 0.0001) and altered myofibre axial elasticity ( P  < 0.0001). Septic myofibres suffered from increased rupturing in a passive stretching protocol (25% more than control myofibres; P  = 0.04), which was associated with impaired myofibre active force generation ( P  = 0.04), linking altered myofibre integrity to function. Sepsis also caused a reduction in muscle titin gene expression ( P  = 0.04) and myosin and actin protein content ( P  = 0.05), but not the myosin‐to‐actin ratio ( P  = 0.7). Conclusions: Prolonged sepsis‐induced muscle weakness may predominantly be related to a disruption in myofibrillar cytoarchitectural structure, rather than to neural abnormalities.